Debating Security in Turkey Challenges and Changes in the Twenty-First Century (LEXINGTON BOOKS, 2013)
Debating Security in Turkey: Challenges and Changes in the Twenty-First Century, edited by Ebru Canan-Sokullu, gives a detailed account of the strategic security agenda facing Turkey in an era of uncertainty and swift transformation in global politics, and regional and local dynamics. The contributors to this volume describe the challenges and changes that Turkey encounters in the international, regional, and national environment at a time of extraordinary flux. This study provides a framework for Turkish security agenda locating it in theoretical discussions, and developing a conceptual framework of security challenges to Turkey, and to a broader region where the country and its interests are located. The book positions Turkey in the new global security order addressing a multidimensional political agenda, and points to the need not only to elaborate on the overall evaluation of Turkey's political affairs--domestic and foreign-- but also to trace a critical conjuncture of transatlantic relations, its recent role in the Middle East, Caucasus and Central Asia, and bid for full membership in the EU within the security context. Finally, the contributors reflect upon where Turkey's security challenges and prospects stand from internal and external perspectives with an interactive foreign policy assessment. Debating Security in Turkey is an essential contribution to the literature of Turkish national security, and the effects of that security in the region